Automatic room temperature control with security system - Ahmad Faris, Zulkifli (2009)
Temperature control is a process to maintain the temperature at certain level. This process is commonly use in all area of the world. Recently in globalization era, this process become important element because there are many applications in daily life involves this process especially server room and green house. Server room works continuously in 24 hours every day. During the process, server room needs to be monitored frequently in order to ensure its functional and efficiency especially on temperature. It is important to study the level of temperature recommended in server room. This matter must be considered to make sure no disturbance occur in server room due to unstable temperature. Automatic temperature control referred as the best method in any application by controlling the temperature automatically. This method shows significant improvement in temperature control as the process is functioning without needed support from the human to control all the process. The result obtain from the process shows the temperature is controlled effectively and more accurate. In addition, this finding makes human works become easy and system that automatically controlled and function will be developed.